Face Centered Cubic Co81.8Si9.1B9.1 With High Magnetocrystalline Anisotropy. Issue 4 (19th February 2018) - Zhang, Jiliang; Shan, Guangcun; Zhang, Yuefei; Ding, Fazhu; Shek, Chan Hung
Abstract : By using the atomic cluster model, face centered cubic (FCC) Co81.8 Si9.1 B9.1 compound is designed and synthesized as ductile single‐phase ribbons successfully. These ribbons show strong orientation along (111) and high magnetocrystalline anisotropy with a coercivity of 430 Oe and squareness of 0.82 at room temperature. The large spin–orbit coupling also contributes to the delocalization of Co 3d band and increased character of itinerant electrons which account for the structural stability and magnetic behaviors. The experimental electronic structure indicates that the magnetic performance can be improved further. This work not only develops a low‐cost Co‐based material for hard magnetic applications, but also extends the atomic cluster model into the design of new crystalline materials. Abstract : New face centered cubic (FCC) Co81.8 Si9.1 B9.1 compound has been successfully achieved based on the atomic cluster model. It exhibits high magnetocrystalline anisotropy due to strong spin–orbit coupling. The stability of the FCC phase and magnetic behaviors are due to the delocalization of Co 3d electrons.